Molecular typing of antibiotic-resistant Staphylococcus aureus in Nigeria. Issue 2 (March 2015) - O'Malley, S.M.; Emele, F.E.; Nwaokorie, F.O.; Idika, N.; Umeizudike, A.K.; Emeka-Nwabunnia, I.; Hanson, B.M.; Nair, R.; Wardyn, S.E.; Smith, T.C.
Summary Background Antibiotic-resistant Staphylococcus aureus including methicillin-resistant strains (MRSA) are a major concern in densely populated urban areas. Initial studies of S. aureus in Nigeria indicated existence of antibiotic-resistant S. aureus strains in clinical and community settings. Methods 73 biological samples (40 throat, 23 nasal, 10 wound) were collected from patients and healthcare workers in three populations in Nigeria: Lagos University Teaching Hospital, Nigerian Institute of Medical Research, and Owerri General Hospital. Results S. aureus was isolated from 38 of 73 samples (52%). Of the 38 S. aureus samples, 9 (24%) carried the Panton-Valentine leukocidin gene (PVL) while 16 (42%) possessed methicillin resistance genes (mecA). Antibiotic susceptibility profiles indicated resistance to several broad-spectrum antibiotics. Conclusion Antibiotic-resistant S. aureus isolates were recovered from clinical and community settings in Nigeria. Insight about S. aureus in Nigeria may be used to improve antibiotic prescription methods and minimize the spread of antibiotic-resistant organisms in highly populated urban communities similar to Lagos, Nigeria.